Neutrophils Enhance Cutaneous Vascular Dilation and Permeability to Aggravate Psoriasis by Releasing Matrix Metallopeptidase 9 - Chen, Jiaoling; Zhu, Zhenlai; Li, Qingyang; Lin, Yiting; Dang, Erle; Meng, Hua; Sha, Nanxi; Bai, Hua; Wang, Gang; An, Shujie; Shao, Shuai (Journal of investigative dermatology, 2021)
Neutrophil infiltration and papillary vessel dilation are hallmarks of the initiation phase of psoriatic lesions. However, how neutrophils aggravate psoriasis development during transendothelial migration and the interaction between neutrophils and cutaneous vascular endothelial cells are less well-understood. In this study, we reported that neutrophils and cutaneous vascular endothelial cells activated each other when neutrophils migrated through the cutaneous endothelial barrier. In addition, neutrophil infiltration into skin lesions caused vascular remodeling including cutaneous vasodilation and enhanced vascular permeability in vivo and in vitro. Microarray gene profile data showed that matrix metallopeptidase (MMP)-9 was overexpressed in psoriatic neutrophils, and zymography assay further validated the bioactivity of MMP-9 secreted by psoriatic neutrophils. Moreover, MMP-9 activated vascular endothelial cells through the extracellular signal‒regulated kinase 1/2 and p38-MAPK signaling pathways, enhancing CD4+ T-cell transmigration in vitro. Correspondingly, an MMP-9 inhibitor significantly reduced cutaneous vasodilation, vascular permeability, and psoriatic symptoms in an imiquimod- or IL-23‒induced psoriasiform mouse model. Overall, our study demonstrates that neutrophil-derived MMP-9 induces cutaneous vasodilation and hyperpermeability by activating cutaneous vascular endothelial cells, thus facilitating psoriatic lesion development, which increases our knowledge on the role of neutrophils in the pathogenesis of psoriasis.